Web-Based Geographic Decision Support System for Boarding House Recommendation Using SMART and A* - Muslimatul Magfirah; Rizal Rizal; Safwandi Safwandi (Politeknik Negeri Batam, 2026)
Selecting a boarding house is an important need for incoming students, especially in urban areas that offer many housing alternatives. The large number of available options often creates difficulties in choosing accommodation that matches user preferences. This study aims to develop a WebGIS-based boarding house recommendation system in Lhokseumawe by integrating the SMART method with the A* algorithm, where the travel distance generated by the A* algorithm is incorporated directly into the SMART evaluation process. The SMART method was used to evaluate and rank boarding house alternatives based on the criteria of price, distance, room size, bathroom type, Wi-Fi, air conditioning, and bed availability, while the A* algorithm was employed to determine the shortest travel route. The system was evaluated through calculation validation by comparing the SMART scores generated by the system with manual calculations, as well as through a preliminary user evaluation. The results showed that the system produced recommendation scores consistent with manual calculations, and the user evaluation indicated that the recommended boarding houses matched user preferences in the evaluated scenarios.